Interference Characterization in Multiple Access Wireless Networks - Irio, Luís Miguel do Rosário (2019)
Contrarily to the point to point wireless link approach adopted in several wireless networks, where a dedicated channel is usually supporting an exclusive-use wireless link, in the last years several wireless communication systems have followed a different approach. In the so called “multiple access wireless networks”, multiple transmitters share the same communication channel in a simultaneous way, supporting a shared-use of the wireless link. The deployment of multiple access networks has also originated the emergence of various communication networks operating in the same geographical area and spectrum space, which is usually referred to as wireless coexistence. As a consequence of the presence of multiple networks with different technologies that share the same spectral bands, robust methods of interference management are needed. At the same time, the adoption of in-band Full-duplex (IBFDX) communication schemes, in which a given node transmit and receive simultaneously over the same frequency band, is seen as a disruptive topic in multiple access networks, capable of doubling the network’s capacity. Motivated by the importance of the interference in multiple access networks, this thesis addresses new approaches to characterize the interference in multiple access networks. A special focus is given to the assumption of mobility for the multiple transmitters. The problem of coexistence interference caused by multiple networks operating in the same band is also considered. Moreover, given the importance of the residual self-interference (SI) in practical IBFDX multiple access networks, we study the distribution of the residual SI power in a wireless IBFDX communication system. In addition, different applications of the proposed interference models are presented, including the definition of a new sensing capacity metric for cognitive radio networks, the performance evaluation of wireless-powered coexisting networks, the computation of an optimal carrier-sensing range in coexisting CSMA networks, and the estimation of residual self-interference in IBFDX communication systems.